Stages of the Development of Foreign Language Education in Secondary Schools of the Russian Empire in the XIXth – at the Beginning of the XX th Century - Svitlana Hmelivska (Pedagogical Discourse, 2013)
The article deals with the stages and peculiarities of education in foreign languages ​​in secondary schools of the Russian Empire in the XIXth – at the beginning of the XXth century.